Risk factors and coronary artery outcomes of coronary artery aneurysms differing in size and emergence time in children with Kawasaki disease - Liu, Jie; Yue, Qiaoyu; Qin, Suyuan; Su, Danyan; Ye, Bingbing; Pang, Yusheng (Frontiers in Cardiovascular Medicine, 2022)
Coronary artery aneurysm (CAA) is a serious cardiac complication arising from Kawasaki disease (KD) and is becoming the leading cause of acquired heart disease in children.The aim of this study was to determine the potential risk factors associated with coronary artery aneurysms (CAAs),which differ in size and emergence time, and track its regression within 3 years of onset. The laboratory data,clinical features, and coronary artery outcomes of patients, who were diagnosed with KD and received treatment from January 2003 to January 2019 were retrospectively analyzed.A total of 484 pediatric patients with KD were examined during the study period.Among them, 130 (26.9%) presented with CAA, including mid- to large-sized CAA in 38 patients (7.9%) and de novo CAA after intravenous immunoglobulin (IVIG) treatment in 22 patients (4.5%). Albumin-to-globin (A/G) ratio was significantly negatively associated with the absolute internal diameter of coronary artery at 1 month of onset and may be used as a predictor of mid- to large-sized CAA development in patients with KD.De novo CAA after IVIG may lead to an increased risk of developing progressive CAA (13 [59.1%] of 22 vs. 31 [28.7%] of 108; P = 0.006) and had significantly greater changes in both the magnitude of CAA dimension variation and maximum z-score of the coronary arteries at 2 and 4 weeks and then 3 months after onset (P < 0.001). Kaplan–Meier survival analysis revealed that the estimated median time of aneurysm persistence was significantly higher in the progressive CAA group than in the non-progressive CAA group (25 vs. 4 months, P < 0.001), as well as among the three groups of patients (giant CAA > medium-sized CAA > small-sized CAA, P < 0.001). Children with KD who had low A/G ratio were more likely to develop mid- to large-sized CAA. Nevertheless, de novo CAA after IVIG treatment may increase the risk of more severe arterial damage and development of progressive coronary artery damage; and both mid- to large-sized and de novo CAA could dramatically prolong coronary artery normalization time. Thus, aggressive risk modifications should be employed, and close monitoring with frequent echocardiography is needed for these patients.